Magnitude and associated factors of thrombocytopenia, among pregnant women at Mizan Tepi university teaching hospital south west Ethiopia - Samuel Sahile Kebede; Tariku Daniel; Asamrew Alemu; Getachew Mesfin Bambo (BMC, 2024)
Abstract Background Thrombocytopenia in pregnancy is a common multifactorial abnormality of the hematological system, next to anemia. It leads to more increased risk of bleeding during delivery, labour, or the postpartum period. Despite being a significant public health concern, there are limited studies done concerning thrombocytopenia during pregnancy. Objective To assess the magnitude and associated factors of thrombocytopenia among pregnant women at Mizan Tepi University Teaching Hospital from September 2023 to November 2023. Methods An institutional-based cross-sectional study was carried out on 230 systematic randomly selected pregnant women who attended antenatal visits from September 2023 to November 2023 G.C using data collection tools. The pretested structured questionnaires were employed to obtain clinical, nutritional, and sociodemographic information. Additionally, three millilitres of venous blood were collected from each participant and analyzed using a Sysmex hematology analyzer. The data was entered into Epidata version 4.6 and analyzed using STATA version 14. Descriptive statistics were computed, and logistic regression was used to identify predictors with a significance level of less than 0.05. Results Two hundred thirty pregnant women participated in the study. Among study participants, the magnitude of thrombocytopenia was 55(24.35%) with 32 (57.14%) mild, 19 (33.93%) moderate, and 5 (8.93%) severe thrombocytopenia. The determinant factors which shown significant association were Malaria parasite infection (AOR 9.27 at 95% CI 7.42, 10.87), one-year Inter-birth interval (AOR 1.7 at 95% CI 1.24, 2.14), History of abortion (AOR 3.94 95% CI 3.13, 4.86), History of hypertension (AOR 3.12 95% CI 1.56, 4.12), HIV infection (AOR 1.81 95% CI 1.32.2.52) and HBV infection (AOR 3.0 95% CI 2.82, 3.34). Conclusion Thrombocytopenia is a public health problem and mild type of thrombocytopenia was the most predominant. The determinant factors that showed significant association with thrombocytopenia were Malaria Parasitic infection, one-year Inter-birth interval, History of abortion, History of hypertension, HIV infection, and HBV infection. Therefore, pregnant women should be continuously screened for thrombocytopenia to avoid excessive bleeding. Increasing Inter-birth interval, preventing abortion as well as timely diagnosis and treatment of underlying causes such as malaria infection, hypertension, HBV, and HIV is important to reduce the burden of thrombocytopenia.